Konsep Penyelesaian Sengketa Tayangan Iklan yang Menyesatkan di Sosial Media - Rizqi Amalia Azizah; Emilda Kuspraningrum; Febri Noor Hediati (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
The development of digital technology has brought significant changes to product marketing and advertising patterns, particularly through social media platforms such as Instagram, which enable the rapid and wide dissemination of information. On the one hand, digitalization provides opportunities for business actors to promote their products in a more creative and interactive way. On the other hand, it also creates the potential for advertisements that may mislead consumers. In practice, there are still business actors who promote products that do not correspond to their actual conditions. Such misinformation can cause losses and raise issues related to consumer rights and the responsibilities of business actors. This study also analyzes dispute resolution related to misleading advertisements on social media. The method used is doctrinal legal research with a statutory approach (statute approach) and a case approach. The results of the study indicate that there are still advertising business actors who neglect consumers’ rights to truthful information about product conditions, and who fail to fulfill their obligations of good faith, providing accurate and honest information, and complying with standards stipulated in laws and regulations. Therefore, it is necessary to strengthen supervision of the implementation of advertising ethics and enforce stricter law enforcement so that consumer rights can be protected and advertising practices on social media can be carried out responsibly.